Role of circadian clock in female embryo implantation - Yukai Zhou; Yukai Zhou; Xiaodie He; Xiaodie He; Zhenxin Chen; Zhenxin Chen; Yucong Gou; Kaixin Zhou; Jinrong Huang; Mei Chen; Jin Hong; Lei Gao; et al. (Frontiers in Cell and Developmental Biology)
Accumulating evidence indicates that circadian rhythm disruption can exert an impact on female reproductive function. In the context of female reproduction, the success of embryo implantation is of utmost significance as it is an essential process for female reproduction. Studies have demonstrated that females with disrupted circadian rhythms are more likely to experience embryo implantation failure, which is exemplified by shift workers, nurses, and flight attendants. Therefore, comprehending the circadian rhythm of female embryo implantation is crucial for human reproduction. Herein, we emphasize the mechanism of circadian operation and its regulatory effect on reproductive hormones related to embryo implantation. More importantly, the regulatory role of peripheral clock genes in the process of embryo implantation (endometrial receptivity and decidualization) is highlighted. Finally, melatonin is hypothesized to be a promising treatment for implantation failure caused by circadian rhythm disturbances.